Analysis of the acceleration profile according to initial speed and positional role in elite professional male soccer players - de Hoyo, M.; Sanudo, B.; Suarez-Arrones, L.; Carrasco, L.; Joel, T.; Dominguez-Cobo, S.; Nunez, F. J. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: The aim of the current study was to analyze the acceleration profile in elite professional soccer players according to their initial speed but also considering players` position. METHODS: Players` accelerations profiles were analyzed using a relative acceleration profile according to the initial speed (S1, from 0 to 7 km/h; S2, from 7.1 to 14.3 km/h; and S3, =14.4 km/h) and the maximum acceleration. RESULTS: Within-group analyzes showed that center backs (CB) performed more high intensity accelerations (likely) when they started in S1 than S2 (effect size [ES] 0.50). Strikers (S) and wide midfielders (W-MD) achieved more accelerations (likely to almost certain) starting in S3 than S1 (ES=0.80 and ES=0.59, respectively) and S2 (ES=0.67 and ES=1.09, respectively). Full backs (FB) completed more accelerations (almost certain) starting in S1 and S3 than S2 (ES=1.39 and ES=1.36, respectively). Finally, midfielders (MD) executed a greater number of high intensity accelerations (likely to almost certain) when they started in S1 than S2 (ES=0.83) and S3 (ES=0.66), and in S3 than S2 (ES=4.72). Between-group analyzes showed that S, W-MD, and FB performed a greater total number of high intensity accelerations (very likely to almost certain) than CB (ES=1.94, ES=1.57, and ES=1.51, respectively) and MD (ES=1.23, ES=0.92; and ES=0.81, respectively). Furthermore, MD performed substantially greater total number of high intensity accelerations (likely) than CB (ES=0.56). CONCLUSIONS: Results suggest that CB achieved more high-intensity accelerations starting in low and moderate speed, S and W-MD in high speed, and FB combined low and high speed.